Incorporation of Indigenous and Local Knowledge in Central Arctic Ocean Fisheries Management - Schatz, Valentin (Arctic Review on Law and Politics, 2019)
On October 3, 2018, the so-called “Arctic Five plus Five” concluded the Agreement to Prevent Unregulated High Seas Fisheries in the Central Arctic Ocean (CAOFA, CAOF Agreement or Ilulissat Agreement). The CAOFA establishes a precautionary framework for the regulation of fisheries in the high seas of the central Arctic Ocean (CAO), including a temporary moratorium on unregulated commercial fishing. The purpose of this debate article is not to discuss the CAOFA’s provisions on fisheries as such, but to take a look at a number of interesting and novel provisions concerning the interests of indigenous and local communities, particularly with respect to incorporation of indigenous and local knowledge into science-based fisheries management in the CAO.